Automatic Physical Database Tuning: A Relaxation-based Approach - Bruno, Nicolas; Chaudhuri, Surajit (Proceedings of the ACM International Conference on Management of Data (SIGMOD), 2005)
In recent years there has been considerable research on automated selection of physical design in database systems. In current solutions, candidate access paths are heuristically chosen based on the structure of each input query, and a subsequent bottom-up search is performed to identify the best overall configuration. To handle large workloads and multiple kinds of physical structures, recent techniques have become increasingly complex: they exhibit many special cases, shortcuts, and heuristics that make it very difficult to analyze and extract properties. In this paper we critically examine the architecture of current solutions. We then design a new framework for the physical design problem that significantly reduces the assumptions and heuristics used in previous approaches. While simplicity and uniformity are important contributions in themselves, we report extensive experimental results showing that our approach could result in comparable (and, in many cases, considerably better) recommendations than state-of-the-art commercial alternatives.